Short-Chain Dehydrogenase NcmD Is Responsible for the C-10 Oxidation of Nocamycin F in Nocamycin Biosynthesis - Mo, Xuhua; Zhang, Hui; Du, Fengyu; Yang, Song (Frontiers in Microbiology, 2020)
Nocamycins I and II, featured with a tetramic acid scaffold, were isolated from the broth of Saccharothrix syringae NRRL B-16468. The biosynthesis of nocamycin I requires an intermediate bearing a hydroxyl group at the C-10 position. A short chain dehydrogenase/reductase NcmD was proposed to catalyze the conversion of the hydroxyl group to ketone at the C-10 position. By using the λ-RED recombination technology, we generated the NcmD deletion mutant strain S. syringae MoS-1005, which produced a new intermediate nocamycin F with a hydroxyl group at C-10 position. We then overexpressed ncmD in E. coli BL21 (DE3), purified the His6-tagged protein NcmD to homogeneity and conducted in vitro enzymatic assays. NcmD showed preference to the cofactor NAD+, and it effectively catalyzed the conversion from nocamyin F to nocamycin G, harboring a ketone group at C-10 position. However, NcmD showed no catalytic activity toward nocamyin II. NcmD achieved maximum catalytic activity at 45 ℃ and pH 8.5. The kinetics of NcmD toward nocamycin F were investigated at 45 ℃, pH 8.5 in the presence of 2 mM NAD+. The Km and kcat values were 131 ± 13 µM and 65 ± 5 min-1, respectively. In this study, we have characterized NcmD as a dehydrogenase, which is involved in forming the ketone group at the C-10 position of nocamycin F. The results provide new insights to the nocamycin biosynthetic pathway.